Template-free synthesis of neodymium hydroxide nanorods by microwave-assisted hydrothermal process, and of neodymium oxide nanorods by thermal decomposition - Phuruangrat A. (2014)
Based on the 150°C and 1 h microwave-assisted hydrothermal reaction of Nd(NO 3) 3 dissolved in deionized water with pH 10 adjusted by concentrated NH 4OH solution, the phase and morphology of the product, characterized by XRD, SEM and TEM analyses, were specified as hexagonal Nd(OH) 3 nanorods 50 nm in diameter and 700 nm long, growing along the [0 0 1] direction. TGA analysis showed the evaporation of adsorbed water and dehydration of Nd(OH) 3 to synthesize the final pure Nd 2O 3 product. With 500°C and 2 h calcination of the Nd(OH) 3 self-template precursor, Nd 2O 3 nanorods were synthesized, retaining both the morphology and growth direction of the precursor. © 2012 Elsevier Ltd and Techna Group S.r.l. All rights reserved.